One-Pot polymerization of dopamine as an additive to enhance permeability and antifouling properties of polyethersulfone membrane - Mulyati, S. (MDPI AG, 2020)
This paper reports the fabrication of polyethersulfone membranes via in situ hydrogen peroxide-assisted polymerization of dopamine. The dopamine and hydrogen peroxide were introduced into the dope solution where the polymerization occurred, resulting in a single-step additive formation during membrane fabrication. The effectivity of modification was evaluated through characterizations of the resulting membranes in terms of chemical functional groups, surface morphology, porosity, contact angle, mechanical strength and filtration of humic acid solution. The results confirm that the polydopamine was formed during the dope solution mixing through peroxide-assisted polymerization as proven by the appearance of peaks associated OH and NH groups in the resulting membranes. The presence of polydopamine residual in the membrane matric enhances the pore properties in terms of size and porosity (by a factor of 10), and by lowering the hydrophilicity (from 69ffi to 53ffi) which leads to enhanced filtration flux of up to 217 L/m2 h. The presence of the residual polydopamine also enhances membrane surface hydrophilicity which improve the antifouling properties as shown from the flux recovery ratio of > 80. Â© 2020 by the authors.